1987
DOI: 10.1111/j.1470-6431.1987.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy audits on home energy consumption

Abstract: The purpose of this study was to examine the impact of energy audits on home energy consumption rate, and to determine factors affecting participation in energy audit/weatherization programmes. Objectives included: (i) developing a linear model for predicting home energy consumption; (ii) examining the role of home energy audits in consumption rate; (iii) determining whether audit participation had increased over a two‐year period; (iv) surveying reasons for non‐participation, and (v) identifying sources of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…A greater proportion of these studies have included number of rooms as a predictor variable in determining household energy usage; fewer studies have used square footage of the residence. Regardless of the method of determining house size all reviewed studies concluded that there is a positive relationship between house size and energy consumption (Gladhart 1984 Several studies have identified age of home as a contributing factor to energy cost and consumption (Chatelain 1981; Jaffee, Houston, and Olshavsky 1982; Junk, Junk, and Jones 1987). The relationship between age of dwelling and energy usage has been found to be both positive and negative.…”
Section: Housing Characteristicsmentioning
confidence: 99%
“…A greater proportion of these studies have included number of rooms as a predictor variable in determining household energy usage; fewer studies have used square footage of the residence. Regardless of the method of determining house size all reviewed studies concluded that there is a positive relationship between house size and energy consumption (Gladhart 1984 Several studies have identified age of home as a contributing factor to energy cost and consumption (Chatelain 1981; Jaffee, Houston, and Olshavsky 1982; Junk, Junk, and Jones 1987). The relationship between age of dwelling and energy usage has been found to be both positive and negative.…”
Section: Housing Characteristicsmentioning
confidence: 99%
“…It has a strong influence on the residential energy usage (Junk, Junk, & Jones, 1987;Lenzen et al, 2004;Morrison & Gladhart, 1976;O'Neill & Chen, 2002;Pachauri, 2004;Tonn & Eisenberg, 2007;Uitdenbogerd et al, 2007;Van Raaij & Verhallen, 1983). The results of a statistical analysis performed by Pachauri (2004) indicate that where the head of the household is in the range of 25-29 years old, the per capita energy requirement is about 7% more than where the household head is less than 25 years old.…”
Section: Householder's Agementioning
confidence: 91%
“…Junk et al (1987) in their research found that increasing levels of education resulted in lower consumption levels. Other studies have also reported formal education as a factor toward energy conservation (Yergin, 1980).…”
Section: Education and Knowledgementioning
confidence: 95%
See 1 more Smart Citation
“…Daarbij zou dan ook nog rekening gehouden moeten worden met de variatie van de pH in de rhizosfeer zoals dat bij teelten in grond vaak wordt gevonden. Ook daarbij worden grote verschillen gemeten (Junk, 1987). Helaas beschikken we niet over dergelijke metingen bij teelten in steenwol.…”
Section: Wpr-811unclassified